Kedudukan Advokat Sebagai Penegak Hukum Dalam Hubungan Dengan Aparat Penegak Hukum Lainnya Untuk Menegakkan Hukum dan Keadilan - Dezonda R. Pattipawae (Faculty of Law, Universitas Pattimura, 2012)
With the enactment of Law Advocate gave an Advocate for proceeds in this country, becausethe existence of the Advocate has been recognized as one of the law enforcement officers whohad not been enacted or not the enforcement of Law Advocates. Role of Advocates as otherlaw enforcement officers are always considered Advocate at the time as an integral part thatdoes not have a strategic position in the system of law in Indonesia. Position advocate for lawenforcement officers to be not a figment, it is proved by the enactment of Law No. 18 Year2003 on Advocates. In Article 5, paragraph (1) expressly says that